2022
DOI: 10.1371/journal.pone.0261114
|View full text |Cite
|
Sign up to set email alerts
|

Sharp increase in inequality in education in times of the COVID-19-pandemic

Abstract: The COVID-19-pandemic forced many countries to close schools abruptly in the spring of 2020. These school closures and the subsequent period of distance learning has led to concerns about increasing inequality in education, as children from lower-educated and poorer families have less access to (additional) resources at home. This study analyzes differences in declines in learning gains in primary education in the Netherlands for reading, spelling and math, using rich data on standardized test scores and regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 19 publications
3
61
0
6
Order By: Relevance
“…Children from low socio-economic backgrounds tend to be particularly affected by forgone learning, alongside policy contexts related to high values of excess mortality, large number of days of school closures and stage of development of digital learning infrastructure (Betthäuser et al 2021 ). Moreover, the learning losses have recently been confirmed by in-depth analysis of standardized test scores, in a work conducted for Netherlands (Haelermans et al 2022 ). Notwithstanding, the learning losses are differentiated against social background, with parental education and income among factors (ibid.).…”
Section: Research Backgroundmentioning
confidence: 74%
“…Children from low socio-economic backgrounds tend to be particularly affected by forgone learning, alongside policy contexts related to high values of excess mortality, large number of days of school closures and stage of development of digital learning infrastructure (Betthäuser et al 2021 ). Moreover, the learning losses have recently been confirmed by in-depth analysis of standardized test scores, in a work conducted for Netherlands (Haelermans et al 2022 ). Notwithstanding, the learning losses are differentiated against social background, with parental education and income among factors (ibid.).…”
Section: Research Backgroundmentioning
confidence: 74%
“…(Van Lancker & Parolin, 2020, p. 243), the long-lasting consequences should not be underestimated (Cantillon et al, 2017). Recent studies showed a sharp increase in inequalities regarding education (Engzell et al, 2021;Haelermans et al, 2022) and student well-being (Prowse et al, 2021). In addition, home schooling caused high levels of parental stress (Malhi et al, 2021).…”
Section: N R E V I E Wmentioning
confidence: 99%
“…Andrew et al (2020);Haelermans et al (2022);Katz et al (2021);Malmusi et al (2022);Nguyen et al (2021);Zachreson et al (2021) Gender Inequalities Women experienced higher rates of mental health issues and psychological deterioration than men.Borrescio-Higa & Valenzuela (2021); Gao, Davillas & Jones (2022); Gibson et al (2021); Utzet et al (2022); Yerkes et al (2020) Women experienced a higher increase in suicide rates than men. Fisher & Ryan (2021); Manun (2021); Nomura et al (2021); Women also more often experienced job loss and/or loss of income than men.…”
mentioning
confidence: 99%
“…Students in low-income communities continually experience deficits which impact the quality of education they receive and ultimately, the trajectory which will lead them from cradle to career. Studies have indicated that there has been a sharp increase in inequality in education since the onset of the pandemic which closed schools in the spring of 2020 (Haelermans, et al, 2022). Results indicate that the inequities in learning lose during the pandemic were directly correlated to parental education and income.…”
Section: Introductionmentioning
confidence: 99%